Trabalho e comércio nos seringais amazônicos - Cherobim, Mauro [UNESP] (Universidade Estadual Paulista (Unesp), 1983)
O trabalho tece algumas considerações acerca das relações seringueiro-seringalista e do sistema de aviamento na estrutura econômica da Amazônia.

Some considerations about the “seringueiro-serigalista” relationship and the “sistema de aviamento” in the Amazon economic structure.
Work and trade in the Amazon rubber plantations
Keywords: Amazonas; Seringais; Sistemas de aviamento; Amazon; Rubber plantations; Amazon economic structure